Biocompatible Porphyrin‐Peptide Conjugates as Theranostic Agents Targeting the Epstein‐Barr Virus. Issue 11 (29th August 2022) - Li, Xiong; Xie, Chen; Zha, Shuai; Tam, Wing Sze; Jiang, Mingjun; Wong, Ka‐Leung
Abstract: Epstein‐Barr virus (EBV) is a common human‐infected virus related to many diseases and cancers. Recently, some peptides have been found to serve targeting and therapeutic roles by inhibiting EBNA1, an oncoprotein of the EBV. We herein report the conjugation of the EBNA1‐targeting peptides and porphyrins which can bring synergistic effects by both introducing more specific treatments (photodynamic therapy) and improving the biocompatibility of the photosensitizer and the peptides. One of our compounds exhibited significant photo‐cytotoxicity where the Lethal Concentration 50 (LC50 )=6.1 μM in EBV‐positive cells. Besides, in vitro cell imaging and co‐staining can also be achieved simultaneously and suggested the binding inside nucleus. Abstract : Porphyrin‐peptide conjugates achieve synergistic theranostic effects specifically on EBV‐positive cells. The biocompatibility of porphyrin could be improved by the introduction of the EBNA1‐inhibition peptide and the inhibition effects were achieved through photodynamic therapy.